Reserves, Liquidity and Money: An Assessment of Balance sheet Policies - Jagjit S. Chadha; Luisa Corrado; Jack Meaning (University of Kent, School of Economics, 2012)
The financial crisis and its aftermath has stimulated a vigorous debate on the use of macro-prudential instruments for both regulating the banking system and for providing additional tools for monetary policy makers. The widespread adoption of non-conventional monetary policies has provided some evidence on the efficacy of liquidity and asset purchases for offsetting the lower zero bound. Central banks have thus been reminded as to the effectiveness of extended open market operations as a supplementary tool of monetary policy. These tools are essentially fiscal instruments, as they issue central bank liabilities backed by fiscal transfers. And so having written these tools into the fiscal budget constraint, we can examine the consequences of these operations within the context of a micro-founded macroeconomic model of banking and money. We can mimic the responses of the Federal Reserve balance sheet to the crisis. Specifically, we examine the role of reserves for bond and capital swaps in stabilising the economy and also the impact of changing the composition of the central bank balance sheet. We find that such policies can significantly enhance the ability of the central bank to stabilise the economy. This is because balance sheet operations supply (remove) liquidity to a financial market that is otherwise short (long) of liquidity and hence allows other .nancial spreads to move less violently over the cycle to compensate.
Keywords: E31; E40; E51; 330; non-conventional monetary interest on reserves; monetary and fiscal policy instruments; Basel III